IMPLEMENTASI PERATURAN KEMENTERIAN PERDAGANGAN TENTANG LARANGAN IMPOR PAKAIAN BEKAS (STUDI KASUS DI TEMBILAHAN) - Aditya, Robi; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Ministry of Trade Regulation on the Prohibition on the Import of Used Clothes is established since 2015, if the implementation of this policy is well implemented it will generate enormous benefits for the Indonesian State especially for the domestic textile industry. According to data from the Ministry of Commerce published in online news Inhil klik.com on Monday, February 9, 2015 mention that the most used clothing storage area in Indonesia is in Indragiri Hilir regency is in Tembilahan. Indragiri Hilir regency, which directly borders neighboring countries such as Singapore, has a great potential to import used clothing so that it needs an intensive and professional handling. Implementation of policies in principle is a way for a policy to achieve its objectives, no more and no less. The problem of this research is how Implementation of Ministry of Trade Regulation on Prohibition of Imported Used Clothes (Case Study in Tembilahan) and What are the factors that hinder the implementation of the policy. The purpose of this research is to know and analyze Implementation of Ministry of Trade Regulation on Prohibition of Imported Used Clothing (Case Study in Tembilahan) and to know and analyze the implementation.The concept of theory that the author uses is policy and policy implementation. And the theory used is Grindle theory with two variables namely policy content and implementation environment. This research uses qualitative research methods with descriptive data assessment. In data collection, the authors use interviews, observation and documentation. By using key information as a source of information.The results of this indicate that the implementation of trade ministry regulations on the ban on imports of used clothing (Case studies in Tembilahan) has not run optimally. The factors which is obstruct the implementation of trade ministry regulations concerning are human resources from the actor of policy, still lack of coordination among related institutions, still lack of financial budger to finance socialization to the target group, economic condition of society, the location of the culture and culture of the people in Tembilahan.Keywords: Policy, Policy Implementation, Prohibition on Import of Used Clothing